On the Cauchy’s Problem for the differential equation of infinite Order - Korobeinik, J. F. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Ю. Ф. Коробейник, О задаче Коши для линейного дифференциального уравнения бесконечного порядкаJ. Korobeinikas, Begalinės eilės diferencialinės lygties Kosi uždavinys